National policy on HIV and AIDS for the education sector in Nigeria - Nigeria. Federal Ministry of Education (Abuja: Federal Ministry of Education, 2005)
This policy provides guidelines for the establishment of good practices for the protection, care and support of learners, teachers and other significant stakeholders in the Education sector on HIV and AIDS disease.
oif 15/04/2019
Nigeriana
Keywords: Acquired immunodeficiency syndrome; AIDS; Human Immunodeficiency Virus; HIV; Nigeria